Preparação e caracterização do sistema magnetoelétrico (x)BiFeO3-(1-x)BatiO3 - Gotardo, Ricardo Augusto Mascarello (2008)
Multiferroic magnetoelectric materials have attracted much attention of the theoretical and experimentalist researchers because they can present, in the same phase, ferroelectric and magnetic orderings. Among them, BiFeO3 is one of the most promising candidate for practical applications, whereas it presents high ferroelectric and antiferromagnetic ordering temperatures. The high electrical conductivity and the low dielectric permittivity are the main problems of working with BiFeO3, beyond the difficult for obtaining single phased materials. For solving these problems, process BiFeO3 with others perovskite structured materials that present high dielectric permittivities, like PbTiO3 and BaTiO3, seems to be an adequate alternative. Taking in mind this assumptions, in this work we processed, by high-energy ball milling, samples of the (x)BiFeO3-(1-x)BaTiO3 system, with 0,9 ≥ x ≥ 0,6, focusing the improvement of the BiFeO3 ferroic properties. The structural and microstructural characterizations had showed the formation of single phase perovskite structured materials. These samples have predominantly the R3c space group. The mean particle sizes of powders reached the nano scale, while the ceramics presented high densification rates with relatively homogeneous grains morphologies. All the processed materials showed antiferromagnetic and ferroelectric orderings at room temperature, which dielectric permittivities higher than that presented by the BiFeO3 compound.